Cracker Times and Pioneer Lives The Florida Reminiscences of George Gillett Keen and Sarah Pamela Williams. - Denham, James M. (University of South Carolina Press, 2000)
"Cracker Times and Pioneer Lives features biographical sketches of more than 280 persons mentioned by Keen and Williams in their writings, many of whom subsequently pioneered settlement in the Florida peninsula."--Jacket.